(untitled) (Scientific Journal of the Dragomanov Ukrainian State University Series 2 Computer-Oriented Learning Systems, 2024)
The article is devoted to the current problem of ensuring web accessibility in the educational environment through the Moodle platform. The importance of accessibility as a tool for removing barriers for students with different needs is considered, and it meets modern international standards, such as WCAG 2.1. Special attention is paid to the role of teachers and administrators of the educational platform in implementing solutions that combine technical capabilities with pedagogical approaches, contributing to integrating the principles of universal learning design. The article analyzes the tools of the Moodle platform that support the creation of accessible content: text materials, multimedia, tables, and interactive elements. The functionality of the Accessibility Checker and Brickfield Accessibility Starter Toolkit plugins, which provide automatic verification of compliance with accessibility requirements, and the Video.js media player, which allows adapting video and audio for students with sensory impairments, is described in detail. The shortcomings and challenges are emphasized, as well as minimal mobile optimization and the need to add subtitles to videos manually. The study aims to develop recommendations for optimizing the use of the Moodle platform to create equal access to education, particularly for students with visual, hearing, or motor impairments. The emphasis is on the importance of combining the platform’s technical capabilities and students’ needs, which allows for creating an environment that not only meets accessibility requirements but also ensures the actual involvement of all participants in the educational process. Further research can be aimed at developing tools for automating the accessibility of web content, integrating Moodle platforms with external services to improve the quality of multimedia, and creating training programs for teachers and administrators of educational platforms on web accessibility issues.